Study to Evaluate and Implement a Comprehensive Approach to the Clinical Assessment and Management of Early Knee Osteoarthritis - Divthane, Rupam (Journal of Biomedical and Pharmaceutical Research, 2021)
Background: Early osteoarthritis (OA) of the knee is characterized by the initial onset of symptoms and early structural changes in the knee joint. The management of early knee OA requires a comprehensive approach that integrates clinical assessment, therapeutic interventions, and ongoing patient education to effectively mitigate symptoms and slow disease progression. Knowledge of the modifiable risk factors associated with knee OA in younger populations indirectly helps earlier identification of individuals at high risk of developing OA and also offers an opportunity to treat them successfully. The combination of advanced diagnostic tools, personalized treatment plans, and patient education leads to better disease management and functional improvements. Ongoing research and adaptation of this approach can further optimize outcomes and provide a model for comprehensive care in early knee OA. Aim: To evaluate the efficacy of an integrated approach to the clinical assessment and management of early knee OA, focusing on a multidisciplinary strategy that combines advanced diagnostic techniques with personalized treatment and self-management strategies. Material and Method: This prospective cohort study was carried out in the outpatient department of Orthopedics at Tertiary care Hospital. Data were gathered from patients visiting the Orthopedic Outpatient Department at the hospital. After analyzing data from 60 participants, it was found that the study sample had a nearly equal distribution of males and females. Data collection involved a structured questionnaire, clinical record forms, and various diagnostic tools. Parameters such as demographic data, biochemical markers, imaging results, and clinical scores (e.g., ACR score, LEFS score, VAS score) were analyzed at baseline, 3 months, and 6 months of follow-up. Advanced imaging techniques, including MRI and ultrasound, were used to assess cartilage changes and joint inflammation. Patients received personalized management plans that included lifestyle modifications, pharmacological treatments, physical therapy, and education on self-management.